Scripture, reason, and the contemporary Islam-west encounter : studying the "other", understanding the "self" - Koshul, Basit Bilal, 1968-; Kepnes, Steven, 1952- (Palgrave Macmillan, 2007)
As a religious tradition of the "East", Islam has often been portrayed as "other" to the Western Traditions of Judaism and Christianity. The essays in this collection use the underlying allegiance to scripture in Islam, Judaism, and Christianity to underscore the deep affinities between the three monotheistic traditions at the same time that respect for differences between the traditions are preserved. The essays are unique in attempting to bring together both contemporary academic and traditional scholarship on scriptural texts to heal the rift between tradition and the contemporary world.